Development of a Management Model for Prevention and Solution of Dropouts among Secondary School Students of Maewin Samakkee School, Chiang Mai Province - Thathong, Suphasit; Tangchuang, Phasina; Pakdee, Chalee (MCU Haripunchai Review, 2026)
This research aimed to 1) study and analyze the administrative status of dropout prevention and resolution, 2) study the administrative model for dropout prevention and resolution, 3) pilot the implementation of the dropout prevention and resolution management model, and 4) evaluate the implementation of the dropout prevention and resolution management model for lower secondary school students at Mae Win Samakkhi School, Chiang Mai Province. The research involved eight key informants. The tools used included interview forms, a process evaluation form, and a satisfaction survey. Basic statistics and content analysis were used. The results revealed: 1) The administrative status of dropout prevention and resolution revealed that the school had an action plan and budget, and staff to care for at-risk students. The school possessed cultural diversity, but there were limitations in student quality, a shortage of specialized personnel, insufficient materials, and a lack of continuity in implementation. 2) The administrative model for dropout prevention and resolution consisted of six approaches: 1) Preventing students from dropping out, 2) Monitoring, 3) Providing support, 4) Correcting students with a tendency to drop out, 5) Retrieving students to return to school, and 6) Failure to track students back into the system. The evaluation results of the model were at a high level. 3) The trial use of the model for developing administrative work on dropout prevention and resolution revealed that the overall results were at the highest level with 9 items and at the high level with 4 items. 4) The evaluation of the use of the model for developing administrative work on dropping out prevention and resolution of lower secondary school students at Mae Win Samakkhi School, Chiang Mai Province, revealed that the overall results were at the highest level.